Investigating the Acute Effects of Hemodialysis on Hemodynamic and Electrocardiographic Parameters: Hemodynamic and EKG Changes in HD - Naseri, Mitra; Kouzegaran, Samanah (Journal of Pediatric Nephrology, 2025)
Background and Aim: Changes in electrocardiographic parameters are reported after hemodialysis (HD). This study determines the alternations in electrocardiographic parameters, hemodynamics, and body weight post-HD. Methods: Electrocardiography was evaluated pre- and post-dialysis in 20 patients (55% males) aged 16.25±6.25 years. Changes in electrocardiographic parameters were compared considering changes in weight (post-dialysis and between dialysis sessions), blood pressure (BP) indices, and the occurrence of intra-dialysis hypotension (IDH). Results: A significant decrease was observed in weight, systolic, diastolic, and mean arterial BPs post-dialysis (P<0.05, for all). No substantial changes in durations of PR interval, QT interval corrected for heart rate, and QRS complex, as well as QT dispersion, were found post-dialysis (P>0.05 for all). Hemodynamic and electrocardiographic alternations were not significantly different between cases with adequate versus inadequate weight gain (P>0.05 for all). Meanwhile, dialysis-induced ventricular strain patterns (ST-T segment changes) were found in 20% of patients, including three cases with inadequate weight gain inter-dialysis. In one case, electrocardiographic findings of hyperkalemia resolved post-dialysis. Whereas, the left ventricular strain pattern appeared in one other case. Conclusion: HD is associated with significant acute changes in systolic and diastolic BP and mean arterial pressure (MAP). These changes, if repeated frequently, can result in myocardial ischemia and infarction. HD protects the heart against hyperkalemia, and thereby arrhythmia; however, it causes ventricular strain patterns, which a predictive of adverse cardiovascular outcomes. Evaluating the long-term complications of hemodynamic and electrocardiogram changes in pediatric HD cases is suggested.